Current and new therapies for mucopolysaccharidoses - Monica Penon-Portmann; David R. Blair; Paul Harmatz (Elsevier, 2023)
The mucopolysaccharidoses (MPSs) are a subset of lysosomal storage diseases caused by deficiencies in the enzymes required to metabolize glycosaminoglycans (GAGs), a group of extracellular heteropolysaccharides that play diverse roles in human physiology. As a result, GAGs accumulate in multiple tissues, and affected patients typically develop progressive, multi-systemic symptoms in early childhood. Over the last 30 years, the treatments available for the MPSs have evolved tremendously. There are now multiple therapies that delay the progression of these debilitating disorders, although their effectiveness varies according to MPS sub-type. In this review, we discuss the basic principle underlying MPS treatment (enzymatic "cross correction"), and we review the three general modalities currently available: hematopoietic stem cell transplantation, enzymatic replacement, and gene therapy. For each treatment type, we discuss its effectiveness across the MPS subtypes, its inherent risks, and future directions. Long term, we suspect that treatment for the MPSs will continue to evolve, and through a combination of early diagnosis and effective management, these patients will continue to live longer lives with improved outcomes for quality of life.